THE TRIGLYCERIDO FATTY ACID FROM HEAT LIPIDS OF PUNTIUS SARANA AND THEIR VARIATION WITH DIFFERENT SIZE - MITRA, RITA; DUA, RAMJI D (Fishery Technology, 2017)
The triglyceride fatty acid components from the heart lipid of Puntius sarana of different sizes have been characterized by thin-layer and gas liquid chromatography. C1 0 to C 24 acids including both odd-numbered and branchedchain acids were detected. The major constituents were ante-iso C 10, C1 0 , C12,2, C14, C, 6’ CI6:J, C17, C1 8 , C1s:b C1s: 2, Cls:3 and C2o:4 while twenty other acids were detected in lower proportion. The composition of these acids and their variation with size of fish have been investigated and discussed.